Using ultrasonography for verifying feeding tube placements in cats - Bruno, Barbara; Savarino, Paolo; Zanatta, Renato; Rallo, Silvia; De Giovanni, Andrea; Maurella, Cristiana; Borrelli, Antonio (Frontiers in Veterinary Science, 2023)
This study aimed to investigate the use of ultrasonography for verifying feeding tube placement in hospitalized cats compared with radiographic evaluation. This prospective investigation was performed on client-owned cats. The position of the feeding tube was checked using right lateral thoracic radiography and ultrasonography. Ultrasound examinations were performed using a high-frequency linear transducer and a microconvex transducer. The examination was performed in three steps: transverse and longitudinal planes of the left side of the animal's neck to identify the feeding tube in the esophagus, and a longitudinal angled plane of the epigastrium to identify the tube at the lower esophageal sphincter. A total of 25 cats were included in this study. Assessing the correct positioning of the feeding tubes using a right lateral thoracic radiograph revealed that the tube was in the distal esophagus in 12/25 cats and reached the stomach in 13/25 cases. In all cats, both ultrasonography and right lateral chest radiography identified the feeding tube at the esophageal level. For stomach, ultrasonography demonstrated good values of diagnostic performance compared to radiography, with excellent reliability and validity in terms of sensitivity and predictive value. Ultrasonography is a valid tool for confirming tube placement in the esophagus and is almost as efficient as radiology.